Low Cost High Gain 8×8 Planar Array Antenna for 5G Applications at 28GHz - Alshortan, H. H.; Alogla, A.; Eleiwa, M. A. H.; Khan, M. I. (Engineering, Technology & Applied Science Research, 2021)
In next-generation mobile networks, hundreds of diverse devices aim to be interconnected, posing huge challenges in capacity, coverage, efficiency, reliability, and connectivity. These and other challenges are addressed at Radio Frequency (RF) parts such as several radiating unit antennas, with very fine beamforming capabilities along with the requirements of high gains and minimized size. This work presents an 8×8 Aperture Coupled Microstrip Patch Antenna (AC-MPA) in the form of a planar array modeled for the 28GHz frequency band with high gain and compact size, making it suitable for 5G networks. The antenna is designed using a substrate with overall dimensions of 74.6×85.648×0.107mm3 and relative permittivity of ε0 = 4.3.